Food Safety Education for Elementary School Students Worldwide - Li-Ling Peng; Allison Childress; John Dawson; Tun-Min Jai; Narissra Maria Punyanunt-Carter; Wilna Oldewage-Theron (Shiraz University of Medical Sciences, 2021)
Context: Foodborne disease is one of the leading causes of early childhood death and childhood diarrhea worldwide. Providing food safety education is believed to be of necessity to prevent foodborne diseases among school-aged students; however, limited studies have addressed food safety education worldwide, particularly for elementary school students. Hence, we conducted this comprehensive review to examine the availability and impact of food safety education for elementary school students worldwide and identify areas that are still needed for future research. Evidence Acquisition: Our inclusion criteria comprised all the studies on elementary school students (aged 5-12) and food safety components that have been published in English between 2010 and 2020, without geographic restriction. In this review project, we utilized nine major data sources, including PubMed, Science Direct, MEDLINE, and CINAHL. Results: Food safety guidelines and educational resources have been established worldwide; however, limited food safety education has been targeted to elementary school students, particularly in developing countries. There is a lack of additional findings concerning food safety behaviors among elementary school students, and insufficient food safety training for teachers. Conclusion: There is an urgent need to provide effective food safety education to elementary school students, which specifically focuses on improving their behaviors. Furthermore, sufficient food safety training and professional development needs to be provided for school teachers.